PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWA PT LEBLE BOGA ADIPERKASA - Satria, Muhammad Rafi Dwi; Iryanti, Endang (POLITEKNIK LP3I JAKARTA, 2026)
This research study aims to examine and analyze the influence of work discipline and compensation on employee performance at PT Leble Boga Adiperkasa. The type of research used is quantitative, with the entire employee population totaling 78 individuals. Due to the relatively small population size, the saturated sampling technique (census) was employed, making the entire population the sample. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via the SmartPLS software. A series of tests were conducted, including validity, reliability, and R-square analysis. The results of the structural model testing consistently prove that both work discipline and compensation are partially confirmed to have a positive and significant influence on the employee performance of PT Leble Boga Adiperkasa.